Principal's Leadership Strategy to Improve School Achievement in the Covid-19 Era: Comparative Study of Two Senior High Schools - Pardosi, Jawatir; Haryaka, Usfandi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
This study aims to describe: 1) the leadership strategy of two school principals, 2) school achievement, and 3) efforts to improve school achievement during the Covid-19 pandemic. This research uses a descriptive qualitative research method. It used snowball sampling. The study was conducted at State Senior High School 1 (SHS) and Catholic High School (CHS). Key informants consisted of 1 principal, one vice principal, three teachers, three education staff, three students, and three parents from each school for in-depth interviews. Data collection techniques were also carried out through observation and documentation studies. The results showed that: 1) in SHS the relationship-oriented leadership pattern stood out, while in the CHS the task-oriented leadership pattern was more prominent, (2) the achievement of both high schools was above the national average; and 3) The Head of SHS forms a learning group based on interests and talents, while CHS forms an innovative virtual achievement group. The results of this study are helpful for school principals as a reference in implementing effective leadership patterns to improve school achievement. The taxonomy of leadership patterns (entrepreneurial, bureaucratic, political, and professional) can be applied to improve school achievement, although there is a different emphasis between the two schools